The domino SWI2/SNF2 Gene Product Represses Cell Death in Drosophila melanogaster. Issue 7 (1st July 2018) - Ellis, Kaitlyn; Wardwell-Ozgo, Joanna; Moberg, Kenneth H; Yedvobnick, Barry
Abstract: The Drosophila domino locus encodes DNA-dependent ATPases of the SWI2/SNF2 class. This class of chromatin remodeler is associated with an array of cellular activities encompassing transcription, replication, repair and recombination. Moreover, domino was observed initially to maintain a repressive chromatin state via genetic interaction studies with homeotic genes. Although domino mutations were also characterized with a cell death phenotype, its association with a death pathway has not been investigated. Here we have used targeted RNA interference to depress domino function in the wing. Resultant wing damage phenotypes were found to be enhanced through overexpression of pro-apoptotic loci, and suppressed through loss of function of these loci. Loss of wing margin and blade tissue was correlated with activation of the effector Caspase Dcp-1, a marker for apoptosis. The affected wing regions also exhibited lower levels of the DIAP1 protein, an inhibitor of apoptosis. The lower level of DIAP1 protein was not correlated with an effect on the activity of a DIAP1 gene transgenic reporter ( thread-LacZ ), suggesting that loss of DIAP1 occurred post transcriptionally. In some cases excessive cell proliferation within the targeted tissue, measured through BrdU incorporation, was also observed. Finally, we used a transgenic reporter construct to monitor the chromatin state upstream of the proapoptotic reaper locus. In genotypes exhibiting targeted domino loss and wing phenotypes, we observed increased reporter activity only in the affected areas. These data support the conclusion that domino normally functions to maintain pro-apoptotic genes in a repressed state.